Cariprazine in the management of emotionally unstable personality disorder in female patients: a case series - Pappa, Sofia; Caldwell-Dunn, Ellice; Kalniunas, Arturas; Kamal, Manzar (Frontiers in Psychiatry, 2024)
Background Emotionally unstable personality disorder (EUPD) is debilitating psychiatric disorder, particularly common in female and forensic populations. However, appropriate pharmacological treatment to effectively manage symptoms of EUPD remains an unmet clinical need. Dopamine receptor partial agonists (DRPAs), such as aripiprazole, have a favourable tolerability profile and have demonstrated some benefits in targeting symptoms of emotional dysregulation, although, evidence regarding the effects of novel D2/D3 DRPA cariprazine in EUPD patients has been limited. Objectives To evaluate the efficacy and tolerability of cariprazine for EUPD in a case series of female forensic inpatients where the diagnosis is more prevalent. Methods Demographic and clinical information of the patients were collected from patient electronic records during their admission in a specialized NHS forensic service. Treatment response was measured using the Positive and Negative Syndrome Scale (PANSS) at baseline, 3 and 6 months and Global Clinical Impression Scale (CGI-scores) at baseline and 6 months. Tolerability and BMI, ECG QTc interval and prolactin levels were recorded prior to initiation and at 6 months. Results Eight female patients with EUPD (mean age 29.8 years, SD 5.3) were treated with cariprazine (range 3–6mg). Total CGI-scores modestly improved from 5.6 baseline to 5.0 at 6 months. There was a reduction in mean total PANSS scores from baseline to 6 months (92.5, SD 8.1 to 72.4, SD 15.8), general psychopathology (56.1 SD 6.7 to 42.5, SD9.7), positive (21.9 SD 4.6 to 17.1, SD4.8) and negative PANSS scores (14.5 SD 6.3 to 12.8, SD4.6), corresponding to a 21%, 23%, 20% and 3% mean score reduction, respectively. Cariprazine demonstrated a favourable metabolic and hormonal side effect profile with no treatment discontinuation at 6 months follow up. Conclusion This is the first case series to evaluate the effectiveness of cariprazine in EUPD. Its efficacy in improving PANSS and CGI-S scores was overall modest and highly variable, reflective of an inherently heterogenous and comorbid patient sample but the benefits on treatment perseverance and tolerability were considerable. Cariprazine may be of particular benefit in EUPD where psychotic symptoms are co-morbid, as an augmentation strategy to clozapine, or where previous antipsychotics have caused metabolic or hormonal side effects.